2020
DOI: 10.11622/smedj.2019096
|View full text |Cite
|
Sign up to set email alerts
|

Timing and predictive factors of developing chronic kidney disease in childhood-onset idiopathic nephrotic syndrome: an Asian experience

Abstract: Online first papers have undergone full scientific review and copyediting, but have not been typeset or proofread. To cite this article, use the DOIs number provided. Mandatory typesetting and proofreading will commence with regular print and online publication of the online first papers of the SMJ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
2
1
0
Order By: Relevance
“…As compared to the patients without complications, those with complications had a significantly higher incidence of ESRD. These rates are also higher than in earlier studies in INS, which reported a CKD prevalence of 3%-10% and an ESRD prevalence of 3.6% during a mean follow-up of 7.70 ± 3.81 years [30]. It supports the conclusion that the development of CKD and ESRD is more common in patients with complications.…”
Section: Discussionsupporting
confidence: 79%
“…As compared to the patients without complications, those with complications had a significantly higher incidence of ESRD. These rates are also higher than in earlier studies in INS, which reported a CKD prevalence of 3%-10% and an ESRD prevalence of 3.6% during a mean follow-up of 7.70 ± 3.81 years [30]. It supports the conclusion that the development of CKD and ESRD is more common in patients with complications.…”
Section: Discussionsupporting
confidence: 79%
“…However, the ESRD rate was only 2.9% in the group without disease or drug-related complications. This gure is higher than those reported by previous studies which reported a CKD prevalence of 3%-10% and an ESRD prevalence of 3.6% during a mean follow-up duration of 7.70 ± 3.81 years [48,49]. This supports the conclusion that the frequency of ESRD was higher in patients with complications compared with the literature.…”
Section: Discussionsupporting
confidence: 66%
“…[ 1 ] The annual incidence rate of childhood nephrotic syndrome is 2–7 cases per 100,000 children aged <16 years (both internationally and locally). [ 2 ] Nephrotic syndrome has many aetiologies, including primary causes (or idiopathic nephrotic syndrome [INS]) such as minimal change disease (MCD), focal segmental glomerulosclerosis and membranous glomerulonephritis, and secondary causes such as systemic lupus erythematosus.…”
Section: Introductionmentioning
confidence: 99%